An assessment of the impacts of renewable and conventional electricity supply on the cost and value of power-to-gas. (12th April 2019) - Hassan, Aymane; Patel, Martin K.; Parra, David
Abstract: Power-to-gas (P2G) is a promising enabling technology for more cross-sector integration but its high cost has so far been a key barrier to implementation. Electricity supply is the greatest contributor to the levelised cost therefore it is important to understand which technologies and strategies can minimise the cost and accelerate the deployment. In this study, a method is devised to evaluate the cost and value of combined systems comprising P2G and renewable energy technologies such as solar photovoltaics, wind and hydro as well as comparing to traditional electricity supply via the wholesale market. The proposed models are based on a temporal resolution of 1 h and include partial operation and ageing throughout the system's lifespan. Our analysis covers both distributed and centralised P2G systems producing hydrogen or methane as well as various value-adding services across different geographies. It is found that the capacity factor of a P2G system drives the economic case and therefore the electricity supply from hydropower plants is economically more attractive than electricity from wind and solar photovoltaic plants in this order. Under today's market conditions, it is highly advisable to combine local renewable supply with wholesale-based supply but interestingly, a 20% capital cost reduction in wind technology or a P2G system efficiency of 80% are break-even points for P2G systems producing hydrogen and connected to wind plants. Graphical abstract: Image 1 Highlights: PV, wind, hydro, conventional wholesale supply and their combinations are assesed. The performance of power-to-gas systems is optimised for each type of supply. The impact of cost and performance improvement trajectories is evaluated. Hydro is the best supply due to high capacity factor and renewable energy content. Wind still requires a 20% CAPEX reduction for plants with capacity factor over 30%.